1995
DOI: 10.1073/pnas.92.23.10457
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of retinal neovascularization in vivo by inhibition of vascular endothelial growth factor (VEGF) using soluble VEGF-receptor chimeric proteins.

Abstract: The majority of severe visual loss in the United States results from complications associated with retinal neovascularization in patients with ischemic ocular diseases such as diabetic retinopathy, retinal vein occlusion, and retinopathy of prematurity. Intraocular expression of the angiogenic protein vascular endothelial growth factor (VEGF) is closely correlated with neovascularization in these human disorders and with ischemia-induced retinal neovascularization in mice. In this study, we evaluated whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
666
2
19

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,145 publications
(712 citation statements)
references
References 24 publications
25
666
2
19
Order By: Relevance
“…Administration of exogenous VEGF 165 prior to exposure to hyperoxia rescued the vessels from hyperoxia-induced apoptosis and vasoattenuation, thus providing hope for the therapeutic use of VEGF or VEGF analogs in preventing regression of vessels in the early phase of ROP (Alon et al, 1995). Likewise, inhibition of VEGF by injection of VEGF receptor chimeric proteins, anti-VEGF antibodies, or antisense oligonucleotides in the mouse model of retinopathy during the neovascular phase has been shown to decrease abnormal blood vessel growth (Aiello et al, 1995b;Adamis et al, 1996;Robinson et al, 2001). …”
Section: Vegf and Abnormal Retinal Vascularizationmentioning
confidence: 99%
“…Administration of exogenous VEGF 165 prior to exposure to hyperoxia rescued the vessels from hyperoxia-induced apoptosis and vasoattenuation, thus providing hope for the therapeutic use of VEGF or VEGF analogs in preventing regression of vessels in the early phase of ROP (Alon et al, 1995). Likewise, inhibition of VEGF by injection of VEGF receptor chimeric proteins, anti-VEGF antibodies, or antisense oligonucleotides in the mouse model of retinopathy during the neovascular phase has been shown to decrease abnormal blood vessel growth (Aiello et al, 1995b;Adamis et al, 1996;Robinson et al, 2001). …”
Section: Vegf and Abnormal Retinal Vascularizationmentioning
confidence: 99%
“…[2][3][4] Blocking of VEGF with antibodies, soluble VEGF receptors (sVEGFR) or inhibition of VEGF receptor (VEGFR) tyrosine kinase activity are useful strategies that have shown promising preclinical and clinical results. [4][5][6] Ranibizumab, an anti-VEGF drug given intravitreally to wet-AMD patients results in substantially improved visual acuity. 7 Intraocular gene delivery of VEGF antagonists could have theoretical advantages over the current treatment, which requires monthly intravitreal injections (for years) by a retinal specialist.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is mounting functional evidence that inhibition of angiogenesis, both non-specifically with pharmacological anti-angiogenic agents and specifically with anti-VEGF agents, ameliorates neovascularisation in well-characterised animal models of retinopathy [5]. Subtle mutations in the 5′ region of the VEGF gene can predispose to diabetic retinopathy, suggesting that regulation of transcription or splicing of the VEGF gene is important in this condition [6].…”
Section: Introductionmentioning
confidence: 99%
“…Subtle mutations in the 5′ region of the VEGF gene can predispose to diabetic retinopathy, suggesting that regulation of transcription or splicing of the VEGF gene is important in this condition [6]. Recent clinical trials of agents that inhibit VEGF have been shown to have some effectiveness in choroidal neovascularisation cause by age-related macular degeneration [7] and in animal models of retinal neovascularisation [5].…”
Section: Introductionmentioning
confidence: 99%